Barrett’s Esophagus in Patients with Gastroesophageal Reflux Disease - Dewan, Khus Raj; Patowary, Bhanumati Saikia; Bhattarai, Subash; Shrestha, Gaurav (Journal of Nepal Health Research Council, 2018)
Background: Barrett’s esophagus a is metaplasia of normal squamous cells that line the lower part of the esophagus and carries a major risk for adenocarcinoma of esophagus. In Asian population, the prevalence of Barrett’s esophagus and adenocarcinoma are less common than in Western countries but has been increasing. Methods: This is a hospital based descriptive study comprising of 120 consecutive patients with symptoms of gastroesophagial reflux disease belonging to both sexes of any age group. The diagnosis of gastroesophagial reflux disease was based on the symptoms like heart burn and regurgitation. Upper gastrointestinal endoscopy was done in all the patients. Four quadrant biopsies were taken from the esophagogastric junction in suspected case of Barrett’s esophagus. The diagnosis of Barrett’s esophagus was confirmed histopathologically. Results: There were 44.2% males and 55.8% females, age ranging from 22 to 85 years mean being 44.33+13.37. Of them, gastroesophagial reflux disease was mild in 54.16%, moderate in 21.16% and severe in 16.66%. Upper Gastrointestinal endoscopy revealed non erosive gastroesophagial reflux disease in 50%, erosive in 45%, hiatal hernias in 5% and Barrett’s esophagus in 1.6%. Both patients with Barrett’s esophagus were elderly and had short segment (<3cm) involvement with no evidence of dysplasia or adenocarcinoma histopathologically. Conclusions: Endoscopic surveillance with detailed inspection and systematic biopsies is recommended for most patients with Barrett’s esophagus. Esophageal carcinoma if detected should be treated at the earliest.